2011
DOI: 10.1007/s10055-011-0196-8
|View full text |Cite
|
Sign up to set email alerts
|

Automated generation of engineering rationale, knowledge and intent representations during the product life cycle

Abstract: One of the biggest challenges in engineering design and manufacturing environments is the effective capture of and decoding of tacit knowledge. Fundamental to Life Cycle Engineering is the capture of engineering information and knowledge created at all stages of the product development process, from conceptual design through to product support and disposal. Consider thisthe amount of vital information and knowledge lost when key design personnel retire-hence the need to capture meta-cognitive task-related stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
(30 reference statements)
0
6
0
1
Order By: Relevance
“…The information required to carry out operations between individual stages of the product lifecycle are described as design process knowledge (Chandrasegaran et al, 2013;Hoisl et al, 2008). One method to capture this is presented in the works of (Sung et al, 2009;Sung et al, 2012). In this case, the commands executed by the user are recorded and documented in an XML file.…”
Section: Design Process Knowledge Capturingmentioning
confidence: 99%
See 1 more Smart Citation
“…The information required to carry out operations between individual stages of the product lifecycle are described as design process knowledge (Chandrasegaran et al, 2013;Hoisl et al, 2008). One method to capture this is presented in the works of (Sung et al, 2009;Sung et al, 2012). In this case, the commands executed by the user are recorded and documented in an XML file.…”
Section: Design Process Knowledge Capturingmentioning
confidence: 99%
“…In general, capturing the design intent requires additional effort during data acquisition. In Sung et al, 2012, for example, the designer is questioned about the respective reason for his executed action during the design process. Other approaches such as the one by Camba et al, 2014 are based on the use of annotations in the CAD model.…”
Section: Design Intent Documentationmentioning
confidence: 99%
“…), based on the principle of unconstrained collision. Robinson et al (2007) and Sung et al (2012) developed a real-time cable assembly routing system named COSTAR based on WTK, using a helmetmounted display, data glove, and position tracker; operators could choose, grasp, or move a cable using a data glove. Liu et al (2014) proposed an interactive cable-routing scheme using augmented-reality technology; users could design and operate virtual models in real 3 D space through an interactive operation algorithm based on an operation panel.…”
Section: Path Planningmentioning
confidence: 99%
“…In this research, a range of different representations are suggested aimed at formalizing this kind of knowledge such as motion trajectory graphs, text instructions, IDEF diagrams, storyboards and annotated video clips. As Sung et al [43,57] have proven in previous research, these formats can be used to represent engineering knowledge both for analysis and investigation and as advice for novice engineers and training of inexperienced personnel. To demonstrate this, the strategy for aligning a component and measuring the true position of a central hole was captured and formalized using different formats.…”
Section: Inspection Planning Strategy Representationsmentioning
confidence: 99%